Gua Kelam - Natashah Md. Nor; Rusli Harun; Amelia Abd. Aziz (Malaysia : UAS Communications (M), 1997)
Exploration of Gua Kelam in Perlis
Executive producer, Najib Shafion, Zabidi Sanip ; script, Amelia Abd. Aziz
Narrator: Reemy Abdul Rahman
Keywords: Caves -- Malaysia -- Gua Kelam (Perlis); Caves -- Malaysia